Conceptual methodologies in agro-environmental systems - Rose, Calvin W.; Adiku, Samuel (Soil & tillage research, 2001)
When continuous measurement of relevant above- and below-ground environmental factors is made, and the dynamics of crop growth and phenology is followed, it is shown that small-plot agronomic experimentation can provide information vital to the development and testing of simulation models. Such models for crops of maize ( Zea mays) and the legume cowpea ( Vigna unguiculata), grown as sole crops and in an intercrop system, were used to simulate yield at two separate sites in the main savanna farming zones in Ghana, West Africa. Simulation was carried out for these three cropping systems using 20 years of historical rainfall data for the two sites, investigating the effect on yield of management options which included time of planting, rate of nitrogen fertilizer application, and crop planting density. The yield results of this series of simulations were then subject to two different types of analysis in order to assist the evaluation of agricultural options for the nation. The first analysis was an economic evaluation based on gross margins, but using the stochastic-dominance technique to rank the profitability of the alternative cropping and management systems. The second, more general methodology employed was multi-criteria analysis (MCA). This analysis covered economic returns and their variability, the amount and quality of residue returned to the soil, and the aerial cover provided by the crop. Other factors which could affect the sustainability of production in the long term, but which could only be evaluated qualitatively, were also included in the analysis, as allowed in MCA methodology. The MCA was then carried out for three scenarios in which different weightings were given to economic outcomes and to factors which are believed to encourage ecological sustainability. These scenarios allow recognition of different priorities which might be given by traditional subsistence farmers as compared to commercial producers. Outcomes of this broad analysis of development alternatives provided scientific support for the traditional Ghanaian practice of grain/legume intercropping which is also widespread in the tropics. The suite of methodologies illustrated by the case study appears to be suitable for the evaluation of alternative farming systems at the scale of a small nation such as Ghana.